KIPRAH POLITIK PARTAI GERINDRA (Studi Tentang Strategi Pemenangan Calon Legislatif Terpilih Partai Gerindra dalam Pemilu 2014 di Kota Salatiga) - Carry Heart Kandowangko; Pamerdi Giri Wiloso; Elly Esra Kudubun (Cakrawala Jurnal Penelitian Sosial, 2014)
Elections (elections) in addition to the circulation succession is understood as a five-yearly political as well as a means of popular sovereignty, and "judgment day." The day of the judgment in question is the decision of the electorate to choose or not choose a candidate and a certain party in the elections. Generra party in Salatiga is a newcomer to accept the consequences of judgment day in the 2009 election in the absence of prospective members that qualify as his legislative members of DPRD Salatiga. But the reality of defeat turned the elections in 2014, with 4 chairs of DPRD of Salatiga. "It's a victory strategy, candidates become relevant for the investigation. Researchers used the concept of habitus, capital, and the realm of actor Pierre Bourdieu as a tool of analysis. This research aims to answer how the strategy of winning candidate elected legislative members from the party of Generra, and factors that affect the winning strategy. research method used was qualitative research with the kind of descriptive and eksplanatory.  Based on the results of the analysis, some important findings in this study are: a). strategy of appeasement actors largely determined by the habitus and capital utilization of economic, social, cultural, and symbolic by the actors; b). capital-capital utilization in order to seize the capital in a field looks in two pattern (the actor uses the power of capital economic, cultural, and symbolic as the base form, build and exploit the network in order to gain recognition and legitimacy of the voters to add and accumulate capital-capital and c). dominant factors affecting the image of the actors is: victory party Gerindra and figure of Prabowo, the image of the actor, and a solid team to win. Keywords: Legislative Elections, Candidates Elected, Generra DPC, Winning Strategies, Habitus, Capital, The Realm Of The Actor